Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight. Issue 7 (24th February 2020) - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael
Abstract: The proton conduction properties of a phosphonato‐sulfonate‐based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water‐mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non‐coordinating water molecules that are part of the crystal structure. Abstract : Anisotropic proton conduction is observed in single crystals of a phosphonato‐sulfonate‐based coordination polymer. Inherent conductivity occurs by proton ′hopping′ through defined paths in the crystal structure. In addition, water‐mediated proton conduction at the crystal surface is identified as an additional effect.